Wild Fluctuations of Random Functions with the Pareto Distribution. (23rd September 2013) - Li, Ming; Zhao, Wei
Abstract : This paper provides the fluctuation analysis of random functions with the Pareto distribution. By the introduced concept of wild fluctuations, we give an alternative way to classify the fluctuations from those with light-tailed distributions. Moreover, the suggested term wildest fluctuation may be used to classify random functions with infinite variance from those with finite variances.